An Analysis Of Thinking Process In Solving Mathematical Problems Looking From The Personality Type In Blended Learning - Setiyaningrum, Desi; Kartono, Kartono; Mulyono, Mulyono (Unnes Journal of Mathematics Education Research, 2020)
The purpose of this study is to test the effectiveness of mathematical solving problems in a Blended Learning environment and to describe the students’ thinking process of mathematical problem solving is looked from the personality type. This research is a mixed methods research with concurrent triangulation design. The results showed that : (1) Learning is implemented effectively with the fulfillment of criteria testing for the achievement of the Minimum Completion Criteria and classical completeness; (2) A student with ESTJ (Extrovert Sensing Thinking Judging) and INTJ (Introvert Intuition Thinking Judging) personality types tend to use the thinking process of forming understanding and opinions with the right and consistent and forming conclusions with precise but inconsistent. The types of ESTP (Extrovert Sensing Thinking Perceiving), ESFJ (Extrovert Sensing Feeling Judging) and ESFP (Extrovert Sensing Feeling Perceiving) tend to use the thinking process of forming understanding, opinions, and conclusions with the right and consistent results. ENFJ (Extrovert Intuition Feeling Judging) types tend to use the thinking process of forming understanding, opinions, and conclusions with precise but inconsistent results. ISTJ (Introvert Sensing Thinking Judging) types tend to use the thinking process of forming understanding and opinions with the right and consistent but have not used the thinking process of forming conclusions correctly. The personality types ISTP (Introvert Sensing Thinking Perceiving) and ISFJ (Introvert Sensing Feeling Judging) tend to use the thinking process of forming an understanding with the right and consistent, forming opinions with the right but have not used the thinking process of forming conclusions correctly.